DA'WAH COMMUNICATION MANAGEMENT OF AL-ARAFAH HAJJ AND UMRAH GUIDANCE GROUP IN IMPROVING PILGRIMS’ UNDERSTANDING OF HAJJ AND UMRAH WORSHIP (Pena Cendekia Insani, 2026)
The pilgrims' understanding of the procedures for the Hajj and Umrah pilgrimage is an important aspect in realizing the implementation of worship that is orderly, independent, and in accordance with the guidance of Islamic law. However, differences in age, educational background, religious experience, and the ability of pilgrims to receive guidance materials pose a challenge for Hajj and Umrah guidance institutions in conveying da'wah messages effectively. This study aims to analyze the da'wah communication management of the Al-Arafah Hajj and Umrah Guidance Group in improving the pilgrims' understanding of the Hajj and Umrah pilgrimage. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of guides or administrators of KBIHU Al-Arafah and pilgrims who participated in the guidance activities. The results of the study indicate that da'wah communication management is carried out through the stages of planning material and manasik schedules, organizing the tasks of guides and administrators, implementing guidance through lectures, discussions, questions and answers, manasik practices, and the use of WhatsApp groups, and evaluating the pilgrims' understanding through practice and direct communication. The research findings confirm that structured, interactive, and adaptive da'wah communication is able to increase the understanding, readiness, self-confidence, and independence of the congregation in carrying out the Hajj and Umrah pilgrimages.